A Study of Customer Orientation and Customer Commitment in the Food Sector of Pakistan - Muhammad Ahmad; Mirza Ashfaq Ahmed (The Lahore Journal of Business)
This study examines the relationship of a firm’s customer orientations, salesperson customer-oriented behavior and customer intimacy with customer commitment. For the purpose of this study, the interpersonal relationship marketing model and the interpersonal attraction investment model are employed to propose the conceptual model. The conceptual model suggests that (1) firm’s customer orientation positively influences the salesperson customer-oriented behavior; (2) salesperson customer-oriented behavior positively influences the customer intimacy; (3) customer-oriented behavior positively mediates between customer orientation and customer intimacy; and (4) customer intimacy acts a positive mediator between the salesperson customer-oriented behavior and customer commitment. Through the course of this study, the proposed conceptual models were tested with the data collected from the firm and customer dyads. Moreover, the data is collected from the food sector of Pakistan. Furthermore, the Smart-PLS is used to test the standardized dyadic data sets. Results have provided substantial support for the proposed conceptual model. There is strong support for the salesperson customer-oriented behavior, and customer intimacy as mediator. Additionally, the results validate the interpersonal relationship marketing model and the Rusbult investment model as well. From a managerial perspective, this study can help organizational policy makers to understand the importance of salesperson behavior, and customer emotions for a long-term relationship with the targeted customer of the specific firm.